2020
DOI: 10.1126/sciadv.abc9294
|View full text |Cite
|
Sign up to set email alerts
|

Touch-induced seedling morphological changes are determined by ethylene-regulated pectin degradation

Abstract: How mechanical forces regulate plant growth is a fascinating and long-standing question. After germination underground, buried seedlings have to dynamically adjust their growth to respond to mechanical stimulation from soil barriers. Here, we designed a lid touch assay and used atomic force microscopy to investigate the mechanical responses of seedlings during soil emergence. Touching seedlings induced increases in cell wall stiffness and decreases in cell elongation, which were correlated with pectin degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 61 publications
3
22
0
Order By: Relevance
“…Ethylene is the first plant growth regulator to be implicated in the response to mechanical stress ( Goeschl et al, 1966 ). More recently, it has been reported that before the seedlings are unearthed, the pressure from the soil stimulates ethylene production and represses polygalacturonase involved in expansion 3 (PGX3) to facilitate seedling emergence from the soil in a dose-dependent manner through the transcription factor EIN3 ( Wu et al, 2020 ). When peg penetrates into the soil, the mechanical stress increases and the light decreases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethylene is the first plant growth regulator to be implicated in the response to mechanical stress ( Goeschl et al, 1966 ). More recently, it has been reported that before the seedlings are unearthed, the pressure from the soil stimulates ethylene production and represses polygalacturonase involved in expansion 3 (PGX3) to facilitate seedling emergence from the soil in a dose-dependent manner through the transcription factor EIN3 ( Wu et al, 2020 ). When peg penetrates into the soil, the mechanical stress increases and the light decreases.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that ethylene plays a remarkable role in growth and developmental changes in a process triggered by mechanical stress ( Goeschl et al, 1966 ; Okamoto and Takahashi, 2019 ; Wu et al, 2020 ). Mechanical stress results in a rapid increase in the amount of ethylene and the activity of 1-aminocyclopropane-1-carboxylic acid (ACC) synthase, which is a key enzyme in ethylene synthesis ( Eisinger, 1983 ; Biro and Jaffe, 1984 ; Emery et al, 1994 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other endogenous phytohormones including gibberellic acid, jasmonic acid, and salicylic acid and light signal also modulate ethylene-regulated apical hook development by influencing the EIN3/EIL1- HLS1 module ( An et al, 2012 ; Zhang et al, 2014 ; Shi et al, 2016a ; Huang et al, 2020 ). Ethylene inhibits hypocotyl elongation by activation of ERF1 pathway, upregulation of WDL5 expression, and downregulation of PGX3 expression via EIN3-dependent signaling pathway ( Zhong et al, 2014 ; Sun et al, 2015 ; Wu et al, 2020 ). Ethylene inhibits root elongation by induction of auxin biosynthesis through upregulating WEI8/TAA1 and ASA1 expression in EIN3- and ARR1-dependent and ERF1-dependent manner, respectively ( Stepanova et al, 2005 , 2008 ; Mao et al, 2016 ; Yan et al, 2017 ).…”
Section: Ethylene Signaling Pathwaymentioning
confidence: 99%
“…WDL5 encodes a microtubule-associated protein that stabilizes the microtubule of cortical cells in the etiolated hypocotyl. In addition, ethylene suppresses pectin degradation and thus enhances cell wall stiffness by EIN3-mediated downregulation of polygalacturonase involved in expansion 3 ( PGX3 ) gene expression ( Wu et al, 2020 ). This EIN3- PGX3 regulatory module contributes to the inhibition of hypocotyl elongation as well as the facilitation of seedling soil emergence.…”
Section: Ethylene Suppresses Hypocotyl Elongation In Response To Soil Barriermentioning
confidence: 99%
“…Furthermore, mechanical signals, as a supracellular mechanism, are well suited to coordinate cell growth and division within tissues and organs. Finally, mechanical signals also feedback on gene activities during morphogenesis (Wu et al, 2020). Growing evidence reveals that morphogenesis requires physical processes in which forces and mechanical properties play a vital role (Uyttewaal et al, 2012;Louveaux et al, 2016).…”
Section: Mechanical-based Morphogenesismentioning
confidence: 99%